Nickel supported ZIF-8.PEG modified catalyst: A designed active catalyst with high H2 productivity in steam reforming of ethanol at moderate temperature. Issue 4 (August 2021) - Razavian, Marjan; Fatemi, Shohreh; Malek mohammadi, Meisam; Nouralishahi, Amideddin
Abstract: Steam reforming of renewable ethanol at moderate temperatures is an attractive alternative for hydrogen production than conventional steam reforming of natural gas which is only feasible at very high temperatures (>650 ℃). Formulating a catalyst for this reaction with ideally dispersed metallic active phase can reduce the activation energy and enhance the activity at moderate temperatures. With this purpose in mind, ZIF-8 with high specific surface area has been nominated as catalytic support in this survey for the dispersion of nickel nanoparticles. The support compositional and interfacial properties were further modified by polyethylene glycol (PEG) to prepare an ideal support with high activity at moderate temperatures. Pristine and modified samples were comparatively characterized by XRD, TGA, BET, FTIR, TEM, FESEM, EDS, AAS, H2 -TPR and NH3 -TPD analyses and catalytically evaluated at 400–450 ℃. TPR profiles of catalysts have demonstrated notable differences in the reduction temperature and quantity of metallic centers which have directly affected the catalytic activity. Lower reduction temperature and higher number of metallic centers were observed for Ni/ZIF-8. PEG which has originated from the tuned interface i.e. high accessibility of nickel centers with highly exposed flower-like structure and lower strength of support/active phase interaction. Thus, Ni/ZIF-8. PEG has revealed considerable improvement in terms of ethanol conversion and H2 yield. At 450 °C, the average H2 yield employing Ni/ZIF-8. PEG catalyst reached 52.6% which was about 16% and 46% higher than those observed by Ni/ZIF-8 and conventional Ni/Al2 O3, respectively. Moderate acidity of the ZIF-8. PEG, higher reducibility of active phase and suitable interfacial interactions have resulted in better performance of this catalyst. Graphical Abstract: ga1 Highlights: Examination of ZIF-8 performance as the catalytic support in ethanol steam reforming. Modification of ZIF-8 compositional and interfacial properties with PEG to enhance the catalytic activity. Considerable improvement in terms of ethanol conversion and H2 yield using Ni/ZIF-8. PEG catalyst. Higher reducibility of the active phase has affected the performance of modified catalyst mostly.